Qualitative Experiential Outcomes of an Undergraduate Nursing Immersion Clinical Experience in El Salvador - Finley, Melissa; Fix, Lauren; Gehring, Courtney; Husnick, Elizabeth; Marvin, Amanda; Parrish, Valerie; Solchenberger, Heidi; Sievert, Clare (My University, 2015)
The purpose of this cultural immersion study was to describe the qualitative experiential outcomes of an immersion clinical experience among UW-Eau Claire undergraduate nursing students who traveled to El Salvador.
Color poster with text and photographs.
Keywords: El Salvador; Cultural immersion; Nursing immersion experience; Nursing clinicals; Posters